Eight Concepts and Practices: Buying and Selling in Islam - Prifty Indah Sari; Emalia Intara Tita; Albizar Albizar (Multidisciplinary Journal of Thought and Research, 2025)
The practice of buying and selling in Islam is one of the important aspects of muamalah which is regulated in detail to ensure fairness, honesty, and blessings in every transaction. Islam establishes basic principles such as the halalness of the goods being traded, the willingness of both parties, and the prohibition of usury, fraud, and gharar (uncertainty) practices. This article aims to analyze how the concept and practice of buying and selling in Islam should be. This research uses a qualitative method with the type of living Quran and hadith research with data sources taken from the arguments of the Quran and hadith, the results of ijtihad, the opinions of experts. The selection of this living Quran method refers to Engkizar's theory which is based on the needs and objectives of the topic under study. The research findings show the concept and eight practices of buying and selling in Islam. i) divinity, ii) willingness, iii) benefit, iv) justice, v) honesty, vi) freedom, vii) morals or ethics, viii) shahih. Overall, this journal describes how the concept of buying and selling in Islamic law, the basic legal concepts in the Qur'an and Hadith, as well as the pillars and conditions that must be met when making buying and selling transactions. Research can be used as a source of reference or knowledge about the principles of buying and selling and can help Muslims in buying and selling according to religious demands and obtaining blessings in the economic activities of the community.